Global, regional, and national burden and quality of care index (QCI) of thyroid cancer: A systematic analysis of the Global Burden of Disease Study 1990–2017. (5th March 2021) - Azadnajafabad, Sina; Saeedi Moghaddam, Sahar; Mohammadi, Esmaeil; Rezaei, Negar; Ghasemi, Erfan; Fattahi, Nima; Aminorroaya, Arya; Azadnajafabad, Reza; Aryannejad, Armin; Rezaei, Nazila; Naderimagham, Shohreh; Haghpanah, Vahid; et al.
Abstract: Background: Thyroid cancer (TC) is the most prevalent malignancy of the endocrine system. Over the past decades, TC incidence rates have been increasing. TC quality of care (QOC) has yet to be well understood. We aimed to assess the quality of TC care and its disparities. Methods: We retrieved primary epidemiologic indices from the Global Burden of Disease (GBD) 1990–2017 database. We calculated four secondary indices of mortality to incidence ratio, disability‐adjusted life years (DALYs) to prevalence ratio, prevalence to incidence ratio, and years of life lost (YLLs) to years lived with disability (YLD) ratio and summarized them by the principal component analysis (PCA) to produce one unique index presented as the quality of care index (QCI) ranged between 0 and 100, to compare different scales. The gender disparity ratio (GDR), defined as the QCI for females divided by QCI for males, was applied to show gender inequity. Results: In 2017, there were 255, 489 new TC incident cases (95% uncertainty interval [UI]: 245, 709–272, 470) globally, which resulted in 41, 235 deaths (39, 911–44, 139). The estimated global QCI was 84.39. The highest QCI was observed in the European region (93.84), with Italy having the highest score (99.77). Conversely, the lowest QCI was seen in the African region (55.09), where the Central African Republic scored the lowest (13.64). The highest and lowest socio‐demographic index (SDI) regions scored 97.27 and 53.85, respectively. Globally, gender disparity was higher after the age of 40 years and in favor of better care in women. Conclusion: TC QOC is better among those countries of higher socioeconomic status, possibly due to better healthcare access and early detection in these regions. Overall, the quality of TC care was higher in women and younger adults. Countries could adopt the introduced index of QOC to investigate the quality of provided care for different diseases and conditions. Abstract : In this study, we retrieved primary epidemiologic data from the Global Burden of Disease (GBD) 1990–2017 database. We produced one unique index, presented as the quality of care index (QCI), to compare different geographical, socio‐developmental, and age scales. The main finding of this survey was the better quality of care among those of higher socioeconomic status, revealing the effect of better healthcare access and early detection in these regions. Also, quality of thyroid cancer care was better in women and younger adults. Evaluation and comparison of thyroid cancer care among various regions and populations, provides data for policy‐makers and healthcare authorities to improve quality of care for patients with thyroid cancer in different settings.